2007
DOI: 10.1592/phco.27.8.1181
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex: A Novel Agent for the Reversal of Neuromuscular Blockade

Abstract: To achieve spontaneous ventilation after completion of surgery, the nondepolarizing effects on skeletal muscle relaxation are often reversed by administration of an acetylcholinesterase inhibitor. However, these agents increase acetylcholine at both the neuromuscular junction and the muscarinic receptors. Therefore, coadministration of an anticholinergic agent is required to prevent parasympathetic adverse effects. In addition, a relative pharmacologic ceiling effect is seen with inhibition of acetylcholineste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Consistent with other studies [1,3,4,8,16], our findings revealed that the profound neuromuscular blockade can be rapidly and reliably reversed by sugammadex in young children aged 1-3 yrs undergoing rigid bronchoscopy. According to Epemolu et al [17] modified cyclodextrins like sugammadex form tightly bound 1:1 complexes with aminosteroid-based muscle relaxants and act as encapsulating drugs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with other studies [1,3,4,8,16], our findings revealed that the profound neuromuscular blockade can be rapidly and reliably reversed by sugammadex in young children aged 1-3 yrs undergoing rigid bronchoscopy. According to Epemolu et al [17] modified cyclodextrins like sugammadex form tightly bound 1:1 complexes with aminosteroid-based muscle relaxants and act as encapsulating drugs.…”
Section: Discussionsupporting
confidence: 92%
“…neostigmine) are injected to speed the rate of recovery from nondepolarizing NMBAs. However, such drugs remain as risk factors for complications such as respiratory depression and hypoxemia which are known as residual block [3]. In addition, muscarinic receptors may be activated by using these agents [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another possibility, this ALN-mediated bone formation could be the direct result of tissues inflammation associated with ALN local administration [24] Since CDs are generally known as biologically inert, it is quiet a surprise to find that ALN-β-CD is bone anabolic. Further literature search found that the only known application of a CD derivative as an active therapeutic agent is sugammadex or Org 25969 (per-6-(2-carboxyethylthio)-per-6-deoxy-γ-cyclodextrin), which was developed as a lead compound for antagonism of prolonged rocuronium-induced neuromuscular block [25][26][27]. While highly water-soluble sugammadex does not have any direct or indirect action on any component of cholinergic transmission, it acts as a solubilized molecular host that complexes with rocuronium and facilitates its movement from the neuromuscular junction back into the plasma, which results in a fast recovery of neuromuscular function.…”
Section: In Vivo Animal Studymentioning
confidence: 99%
“…This substance is used in adults of normal weight at 2mg/kg to promote reversion of moderate NMB, measured by the train-of-four (TOF) stimulus sequence (T4/T1 ≥0.9); at 4mg/kg for reversal of deep NMB; and at a dose of 16mg/kg for immediate reversal of rocuronium-induced NMB [9][10][11][12][13] . Previous studies have suggested that reversal of NMB in morbidly obese patients could be achieved at 4mg/kg for deep blockade considering the ideal body weight, or 2mg/kg, regardless of which body weight is considered, ideal or actual 18,19 .…”
Section: Introductionmentioning
confidence: 99%